Reinvigorating the Concept of a Situation in Situational Judgment Tests. Issue 1 (23rd March 2016) - Brown, Nicolas A.; Jones, Ashley Bell; Serfass, David G.; Sherman, Ryne A.
Abstract : What is the role of the situation in situational judgment tests (SJTs)? Lievens and Motowidlo (2016 ) assert that SJTs are somewhat of a misnomer because they do not actually measure how individuals would behave in a given situation per se. According to these researchers, SJTs assess general domain knowledge—whether potential employees recognize the "utility of expressing certain traits" (p. 4). As a result, SJTs map onto personality measures, which are a summary of behavior across time and situations. SJTs provide predictive validity in part because they tap into personality. However, rather than renaming SJTs, it is possible to reintroduce the concept of a situation to provide even greater predictive power. Thus, the goals of this commentary are to (a) clarify what constitutes a situation, (b) describe what SJTs might actually measure, and (c) set forth a path for a taxonomy of workplace situations.